Strategies in Developing Freshwater Fish Farming to Prevent Stunting - Liufeto, Franchy Ch.; Rosnah, Upik S.; Adhar, Damianus (International Journal Labs, 2023)
Background: Timor Tengah Selatan is home to some of the most common malnutrition problems in Indonesia. The high rate of stunting in Timor Tengah Selatan is caused by food availability, climate and lack of knowledge about stunting itself. Additionally, the rural nature of the region, its high water demand, poor road infrastructure, and lack of visibility for health workers are significant factors. Therefore, there is a need for efforts to achieve success in fighting stunting, one of which is the strategy of developing freshwater fish farming to overcome stunting in Timor Tengah Selatan. Aim: The research would like to analyze strategies in developing freshwater fish farming to prevent stunting in Timor Tengah Selatan. Method: This research is a type of qualitative descriptive research, while data collection techniques are carried out by exploring journals and other information relevant to the study. Findings: The results of the study show that the strategy for developing freshwater fish farming to overcome stunting in Timor Tengah Selatan is by increasing business and creating additional income for the community as well as encouraging the development of freshwater aquaculture to replace the decline in marine fish during difficult times. It will improve the economy of the region which is also supported by an increase in fishermen's income.